AN ANALYSIS OF EXPLICITATION IN THE NOVEL PEMBUNUHAN DI MALAM NATAL - Sentana, Aswarini (Universitas Gunadarma, 2020)
This is a linguistic research of translation which presents an analysis of explicitation in the novel entitled Pembunuhan di Malam Natal which is the Indonesian translation of Agatha Christie’s Hercule Poirot’s Christmas. The purposes of this research are: (1) to find out what types of explicitation occurred in the novel Pembunuhan di Malam Natal and (2) to find out what the reasons of the explicitations. The method used in this researcher is a qualitative method through library research. The researcher takes the first 50 data of explicitation found in the translation and analyzes them using the concept of explicitation by Murtisari (2013) which is based on the Relevance Theory. In identifying the reasons of explicitation, the researcher uses the theory by Larson (1984). The results of this research show that the types of explicitation found in the novel Pembunuhan di Malam Natal are scalar and categorical explicitation. Whereas, the reasons of explicitation identified are the necessity for correct and clear expression of the source meaning, the needed for naturalness of style or to create the same emotive effect as the source text, and to explicate the truly implicit information in the source text. There is no explicitation due to the requirement for the grammar of the target language is because of the fact that English language has more specific grammar rule, i.e., tenses than Indonesian language’s rule. Thus it can be concluded that what occurs in case of grammar between the source text and the target text is instead implicitation, not explicitation.